Reintroductions of Forest Fauna in the Second Polish Republic - Daszkiewicz, Piotr (Studia Historiae Oeconomicae, 2024)
The article presents the action of the reintroduction of forest fauna conducted in the interwar period in Poland. The activities that led to the rescue of bison were discussed. The success of saving the last beaver populations in this part of Europe was recalled and analyzed. The activities, pioneering in Europe, carried out by the State Forests, for the protection of moose, were also presented. The article draws attention to the modernity of the ecological policy in Poland during the period of 1918–1939, as well as to the importance of the policy implemented by the State Forests in this period. Despite the Soviet-German occupation of Poland, some of the activities of interwar Poland managed to survive and to this day constitute an important part of the ecological policy of the EU.